Step, Servo and Hub Motor Based Hybrid PCB Processing and Prototyping Device Design and Analysis - Yerli, Atakan; Aliew, Fuad; Machado, José Mendes; Saebra, Eurico Augusto Rodrigues; Caetano Monteiro, A. Alberto Caetano (Springer Science and Business Media Deutschland GmbH, 2023)
Aim of this research is to design the central processing unit, which is indispensable today, with 3 different motor types and to control the ideal motor in ideal torque and rpm units in the market, and to complete the process with the same precision with the minimum unit required in the energy and time domain. The stepper motors used in the hobby and light industry sector in the market offer a 2% step-miss sensitivity and have minimum energy consumption, while the servo motors have low energy efficiency against 1/10000 step-miss sensitivity and the high rpm speeds of magnetic hall sensor hub servo systems and the sensitivity that is the same as servo motors. The mission of this research is to establish a system that can respond to the increasing prototyping demands in the domestic market due to the exchange rate by making comparison analyzes of the principles in the energy and time domain. In this research one of another purpose is designing hybrid machine with 3D Printing abilities and CNC PCB prototyping abilities under the same chassis. In this research the parts that used had been chosen to form available market products in Turkey. In this research another software explained detailly with advantages and disadvantages in any perspective. © 2022 Elsevier B.V., All rights reserved.
International Conference on Reliable Systems Engineering, ICoRSE 2022 -- Virtual, Online -- 282469
Keywords: CNC; FDM; Hub motor; Hybrid systems; Klipper; Servo motor; Step motor